The Analysis of Large Dam Impacts on Sediment Grain Size Distribution in a Tropical River System - Mohammad Noor Amal Azmai; Mohd Hafiz Rosli; Mohammad Haroon Hairan; Nor Rohaizah Jamil; Ley Juen Looi; Ahmad Zaharin Aris (Civil Engineering Journal, 2023)
Sedimentation is a natural phenomenon of rivers that is enhanced by modification of the river basin. The presence of dams delays the exchange of sediments, nutrients, and organisms between the terrestrial and aquatic environments. This article assesses the impact of the Selangor dam on the sediment grain size distribution and its association with river velocity and discharge. The fieldwork for sampling is conducted in the normal and rainy seasons. The samples were analyzed through a sieve analysis procedure to determine the particle size of the sediments. After the sieve analysis technique, GRADISTAT analysis was performed on the output. The GRADISTAT analysis classifies the sediments between sandy gravel and sand, and the median grain size (D50) ranges from 4.00 to 0.18 mm. The spatial distribution of the D50 shows that the bed-load sediments of the upper Selangor River are becoming fine-grained downstream. The skewness of the sediments differs from 0.86 to 8.44, which indicates that the sediments are poorly to moderately well sorted. The Spearman's correlation of the D50 and river velocity and discharge determine no association of the D50 with river velocity and discharge. The stations near Selangor Dam have high slopes and receive "sediment hungry" water that washes small-sized sediments; therefore, the upper stations have a more significant amount of gravel and large sand. Doi: 10.28991/CEJ-SP2023-09-02 Full Text: PDF